How to Make Real Money in Second Life : Boost Your Business, Market Your Services, and Sell your Products in the World's Hottest Virtual Community - Freedman, Robert, 1960- (New York McGraw-Hill, 2008)
Second Life has mushroomed from a small group web experts and graphic designers to a sprawling megalopolis of four-and-a-half million residents. This work shows how players, have begun to tap the business opportunities available in Second Life. It explains how you can apply your real-world business know-how to make a killing in this environment
Include Illustration
Keywords: Second Life (Game) -- Computer simulation -- Shared virtual environments